A RELATIONSHIP OF CO-DEPENDENCE AND STRESS COPING STRATEGIES FOR WOMEN IN RELATIONSHIP WITH PARTNER OF SUBSTANCE USE DISORDER - Lāce, Aiva; Sudraba, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
This study aim is to explore the relationship between coependency and coping strategies of women in relationship with an individual addicted to psychoactive substances. The study included 31 women aged 25 to 64 years (M = 42.03; SD = 9.45). Three surveys were used in the study - Socio-Demographic Data Survey; Spann-Fischer Co-dependence Scale; The Ways of Coping Scale. Spearman's correlation analysis was used to determine the liabilities, and the prediction of coping strategies / ways of indicators was performed by linear regression analysis.It was found that there is a statistically significant relationship between codependency and emotion-focused coping as strategy (strategic problem- solving, escape and avoidance, taking responsibility). Research on current coping strategies has shown that emotion-focused coping as strategy and corresponding types of stress management such as seeking social support, positive reassessment, planned problem solving and escape and avoidance are more often used.